First records of hypopigmentation of Tayra Eira Barbara in Colombia - Aya-Cuero, Carlos A.; Molina-Vargas, Brayan A.; Stasiukynas, Diana C.; Páez, Mónica; Pantoja-Peña, Gabriel; Cáceres-Martínez, Carlos H.; Pardo, Lain E. (Therya Notes, 2025)
Leucism, xanthism, and piebaldism are genetic conditions that generate deficiency in animal melanin deposits or hypopigmentation, which can manifest in the total or partial absence of pigmentation in the integumentary tissue. In Colombia, there are few records of this condition in mammals such as bats and rodents. Nevertheless, this condition also occurs in mustelids, and the information is scarce for any biogeographic region of Colombia. We used data derived from different surveys with camera trap studies across 5 departments in 2 biogeographic regions in Colombia (Andean and Orinoco). The species was identified by external characteristics and the color aberrations following specialized literature. With a sampling effort of 11,015 camera/days, and one ad libitum observation, we described 10 cases of hypopigmentation in tayras which might be related to leucism, xanthism, and white spots or piebaldism. In addition, other abnormalities such as taillessness and light gray coloration were found. Our records constitute the first documented cases of hypopigmentation of tayras in Colombia and analyzed evidence of potential anomalies in wild populations living in transformed habitats. We intended to highlight these particular colors of the phenotypes in the species as a consequence of genetic mutations and environmental pressures. Finally, we also complement some aspects of their natural history.